Euthanasia in Uruguay and Its Regional Impact - Sebastiani, Mario (Revista del Hospital Italiano de Buenos Aires, 2025)
The legalization of euthanasia in Uruguay prompts an ethical and legal debate on autonomy and dignity. While Argentina maintains legal and cultural barriers, the academic discussion is growing. Uruguay’s experience shows a model centered on individual rights and could guide future reforms in our country.